Peranan Polisi Republik Indonesia dalam Pemberantasan Praktik Illegal Fishing di Wilayah Perairan Indonesia - Jepry Robin; Parasian Simanungkalit; Anwar Sadat (Syntax Literate, 2023)
Coral reefs owned by the State of Indonesia are approximately 7000 km2 with 480 species of coral that have been successfully described and have a diversity of fish around 1,650 species of fish. Foreign fishermen who often enter Indonesian territorial waters, among others, come from Thailand, Vietnam, the Philippines, and Malaysia. Natuna waters, North Sulawesi waters are the most vulnerable area to illegal fishing activities. The vulnerability of Indonesian waters from illegal fishing activities, in addition to the fact that the water area contains the potential for large fishery resources, also because the geographical position of the Indonesian territorial waters is in international waters so that it is very open to the possibility of foreign fishermen entering Indonesian waters and fishing illegally. Illegal fishing activities still occur in Indonesian waters, despite various efforts to overcome them by the Indonesian government. This cross-border illegal activity is not only a problem for Indonesia, but also an interstate problem considering that the perpetrators and activities are transnational, and therefore, the handling must also be carried out cross-country, especially through bilateral cooperation with neighboring countries in the region where fishermen often enter Indonesian territorial waters illegally. Illegal fishing has become a global concern because this illegal activity has taken place in various regions and is considered to threaten the existence and sustainability of global marine fisheries resources if not handled seriously by the international community. In the study of international relations, illegal fishing can be categorized as a form of transnational crime, because in these illegal activities contained several aspects as included in the definition of transnational crime.